Avaliação do estresse oxidativo e nitrosativo no fígado de ratas senescentes tratadas com frutose - Almeida, Beatriz Zocoler de [UNIFESP] (2017)
Introduction: Ageing is a multifactorial process caused by the progressive decline in physiological functions. According to IBGE (Instituto Brasileiro de Geografia e Estatística), Brazil's current population has 23.5 million of elderly. Oxidative/nitrosative stress is the resultant of an imbalance between the formation and removal of oxidizing agents in the body due to excessive generation of reactive oxygen species (ROS) and reduction of endogenous antioxidants. ROS are related to ageing by free radical theory. High levels of ROS and oxidative stress induce apoptotic cell death mechanisms leading to cell and tissue damage. The liver is a major organ attacked by ROS. Objective: The aim of this study was to evaluate oxidative and nitrosative stress in liver of senescent rats treated with fructose. Methods: 40 Wistar rats, females, 20 adult with 4 months age (A) and 20 senescent with 24 months age (S), which received water or fructose (FRU) for 12 weeks, were allocated to the following groups: A+Water, A+FRU, S+Water and S+FRU. The metabolic profile (food and water consumption, and body weight) was monitored during the treatment period. At the end of the experiment, the animals were killed by decapitation and plasma was collected for analysis of liver function alanine aminotransferase (ALT) and aspartate aminotransferase (AST). The liver tissue was removed for analysis: reactive substances to thiobarbituric acid (TBARS), nitric oxide (NO), superoxide anion, catalase (CAT), superoxide dismutase (SOD), the total glutathione, endothelial nitric oxide synthase (eNOS), caspase-3, nitrotyrosine and histology. The results were described as mean (±) standard error (SE), using one-way ANOVA with Tukey or Kruskal-Wallis post-test and statistical significance was defined as P<0.05. Results: In the metabolic profile, food intake in S+Water group was significantly reduced compared to A+Water group; in water consumption, the group A+FRU was significantly increased compared to group A+Water, and S+FRU group was significantly higher compared to S+Water. In relation to body mass, liver function and NO there was no significant difference among the groups. TBARS levels were significantly decreased in the S+FRU vs. A+FRU and S+Water groups and superoxide anion was significantly elevated in S+FRU when compared to A+FRU and S+Water groups. There was no significant difference among the groups in the levels of SOD and CAT; for total glutathione, we noted that the S+FRU group was significantly decreased compared to group A+FRU. Protein expression of eNOS in S+Water group was significantly reduced compared to group A+Water and significantly increased in group S+FRU vs. S+Water. It was observed that the expression of nitrotyrosine was significantly increased in the group S+FRU vs. A+FRU and S+Water. The expression of caspase-3 showed a significant increase in the S+FRU group when compared to A+FRU, followed by higher rate of apoptosis in the liver of animals that consumed fructose, mainly in S+FRU group, which also had greater evidence of hepatic steatosis. Conclusion: Fructose contributes significantly to increase the oxidative and nitrosative stress and to a higher rate of apoptosis in aged animals, suggesting that diets rich in sugar can cause irreversible damage to the body during ageing.